Research and practice of characteristic teaching resources sharing and interactive platform - Yun, W. (Journal of Digital Information Management, 2012)
By using advanced cloud computing, virtualization and distributed video load balance technology, the paper constructs an interactive platform which shares the teaching resources. On the one hand it provides a beyond time and space, free and equal interactive teaching and learning platform for the teachers and students. On the other hand it offers teaching resources Networked storage, utilization, communication and show space. Dispersive resources will be classified automatically and integrated modularly in order to perform Characteristic and high-quality multimedia resource database and media teaching characteristic of material database.
Keywords: Characteristic teaching resource; Interactive platform; Sharing